The Martini Club: The Spy Coast - Book 1 - Gerritsen, Tess (Thorndike, Maine : Center Point Large Print, 2024)
When a body turns up in her driveway, former spy Maggie Bird, forced into retirement after a mission went tragically wrong, turns to her "Martini Club" of former spies to help her uncover the truth about who is trying to kill her, and why.
Keywords: United States. -- Central Intelligence Agency -- Officials and employees; Fiction; Women spies -- Fiction; Retirees -- Fiction; Book clubs (Discussion groups) -- Fiction; Murder -- Investigation; Fiction; Police -- Fiction; Maine -- Fiction; Spy stories; Suspense fiction; Thrillers (Fiction); Large print books